MEANING, IMPORTANCE, ROLE OF TEACHERS, SUGGESTIONS AND CHALLENGES OF VALUE EDUCATION IN THE 21ST CENTURY. - Kumar, मुरारी; Pathak, राम कुमार (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Values ​​are the capital of knowledge on which Indian culture is based. Values ​​are present in every choice, determination, decision and work of man. It is very essential for human existence. It is a code of conduct or inclusion of virtues by adopting which a person develops his personality and emerges as influential and trustworthy in the society. Values ​​include human perceptions, thoughts, beliefs, attitude and faith etc. Being valuable and valueless proves the usefulness and uselessness of every thing. The importance of values ​​is accepted in every situation. Man is a social animal. His values, his qualities, his good tendencies make him different from animals and birds. Just as a fish without water, a body without a platform and thoughts without language are meaningless, similarly life is meaningless without values. Value education teaches us the values ​​of life like justice, charity, kindness, sympathy, honesty, mutual goodwill etc.